DIETARY FATS AND OILS: KNOWLEDGE AND PREFERENCES OF SCHOOL-AGED CHILDREN IN GREECE - ZIMVRAKAKI, ELENI; Makris, G.; Athanasiou, Kyriakos (Mediterranean Journal of Educational Studies, 1997)
Abstract - The study described in this paper investigates the knowledge and preferences of 176 Greek children, aged between nine and eleven, with regard to fats and oils. The results show that the majority of children cannot classify oils. butter, and margarine in the correct nutritional category. The great majority were of the opinion that it is healthier to use olive oil, rather than than seed oils, for salads and cooked meals. However, they also answered that seed oils are healthier than olive oil for fried meals. No statistically significant differences between the sexes was found in the answers, except for their preferences regarding the use of olive oil in cooked meals and salads. The results indicate that Greek children lack the information they need to make healthy food choices. In addition, there is a need to develop teaching strategies thatfocus on lipids and their impact on health.